Pembentukan Customer Satisfaction dan Customer Loyalty pada Layanan Mobile Banking - Malya Nadhira Azra; Usep Suhud; Meta Bara Berutu (Teewan Journal Solutions, 2026)
This study aims to broaden insights and analyze the influence of security, relative advantage, and convenience on customer satisfaction and customer loyalty in the use of Livin' by Mandiri mobile banking services among Generation Z users. This research employed a quantitative approach with data collection conducted through an online survey using a structured questionnaire. The target population in this study consisted of Generation Z individuals residing in the DKI Jakarta area. The sampling technique used was purposive sampling, with a total of 276 respondents. Data analysis techniques included validity and reliability testing, as well as hypothesis testing using Structural Equation Modeling (SEM) AMOS version 26. The results of hypothesis testing in this study obtained, that it is proven 1) security has a positive and significant effect on customer satisfaction, 2) relative advantage has a positive and significant effect on customer satisfaction, 3) convenience has a positive and significant effect on customer satisfaction, 4) security has a positive and significant effect on customer loyalty, 5) relative advantage has a positive and significant effect on customer loyalty, 6) convenience has a positive and significant effect on customer loyalty, 7) customer satisfaction has a positive and significant effect on customer loyalty.